ANALISIS TERHADAP AKAD MUSYARAKAH MUTANAQISAH DAN PROBLEMATIKANYA DALAM PRAKTIK PERBANKAN SYARIAH - Makraja, Fahmi; Elya Fitriyani; Nisa Afifah; Khadijatul Musanna (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2025)
The Musyarakah Mutanaqisah (MMQ) contract, as one of the increasingly popular financing products in Islamic banking, offers a unique alternative to asset ownership that is in line with sharia principles. This study aims to comprehensively analyze the MMQ contract, highlight its Sharia foundations, and identify and explore the issues that arise in its implementation in the field. The research methods used include literature review and qualitative analysis of fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), Islamic banking regulations, and practices observed in several Islamic banks. The analysis shows that, in theory, MMQ is built on three basic contracts that do not conflict with each other: the syirkah or musyarakah contract for partnership, the ijarah contract for lease, and the sale and purchase contract for transfer of ownership. The combination of the three forms an innovative financing structure. However, in practice, several crucial issues arise. One of these is the issue of al-Ijarah al-Mawsuqah bil-Bay', or lease followed by a promise of sale, which some contemporary scholars still debate its validity. Nevertheless, the DSN-MUI has issued a fatwa permitting this scheme under certain conditions and terms